Priority Activities for Implementing Industry 4.0—The Case of Serbia - Sonja Đuričin; Isidora Beraha (Proceedings, 2023)
The industry 4.0 concept is essential to fostering innovation and promoting economic growth. Its successful implementation involves the entire innovation ecosystem, as defined by open approaches to innovation, which emphasize collaboration among various actors in the innovation system. The efficiency and intensity of interactions between different actors determine the innovation activity needed for industry transformation. The integration of technologies is at the heart of Industry 4.0. By conducting a survey among the most important actors in the innovation ecosystem, this research identifies priority activities for implementing the concept in Serbia.